Upregulation of the ESCRT pathway and multivesicular bodies accelerates degradation of proteins associated with neurodegeneration - Ron Benyair; Sai Srinivas Panapakkam Giridharan; Pilar Rivero-Ríos; Junya Hasegawa; Emily Bristow; Eeva-Liisa Eskelinen; Merav D Shmueli; Vered Fishbain-Yoskovitz; Yifat Merbl; Lisa M Sharkey; Henry L. Paulson; Phyllis I Hanson; et al. (Autophagy Reports, 2023)
Many neurodegenerative diseases, including Huntington’s disease (HD) and Alzheimer’s disease (AD), occur due to an accumulation of aggregation-prone proteins, which results in neuronal death. Studies in animal and cell models show that reducing the levels of these proteins mitigates disease phenotypes. We previously reported a small molecule, NCT-504, which reduces cellular levels of mutant huntingtin (mHTT) in patient fibroblasts as well as mouse striatal and cortical neurons from an HdhQ111 mutant mouse. Here, we show that NCT-504 has a broader potential, and in addition reduces levels of Tau, a protein associated with Alzheimer’s disease, as well as other tauopathies. We find that in untreated cells, Tau and mHTT are degraded via autophagy. Notably, treatment with NCT-504 diverts these proteins to multivesicular bodies (MVB) and the ESCRT pathway. Specifically, NCT-504 causes a proliferation of endolysosomal organelles including MVB, and an enhanced association of mHTT and Tau with endosomes and MVB. Importantly, depletion of proteins that act late in the ESCRT pathway blocked NCT-504 dependent degradation of Tau. Moreover, NCT-504-mediated degradation of Tau occurred in cells where Atg7 is depleted, which indicates that this pathway is independent of canonical autophagy. Together, these studies reveal that upregulation of traffic through an ESCRT-dependent MVB pathway may provide a therapeutic approach for neurodegenerative diseases. Abbreviations: AD: Alzheimer’s disease CLEAR: Coordinated Lysosomal Expression and Regulation HTT: Huntingtin HD: Huntington’s disease MEF: Mouse embryonic fibroblasts HTT: Mutant Huntingtin MVB: Multivesicular bodies TFEB: Transcription factor EB